Pengaruh Modal, Tenaga Kerja dan Bahan Baku Terhadap Produksi UMKM Batik Kabupaten Pamekasan (Studi di Kecamatan Proppo) - Zahrah, Kinnatus; Listiana, Yufita (Buletin Ekonomika Pembangunan, 2025)
Production is significant in an industry and requires constant planning and supervision. By paying attention to the factors that affect production, it will make it easier to run an industry. This study aimed to analyze the effect of capital, labour and raw materials on the production of batik MSMEs in Proppo District, Pamekasan Regency. The research method used is descriptive with a quantitative approach. The sampling technique with non-probability sampling in this study used purposive sampling. The number of samples used in this study amounted to 98 respondents, determined using the Slovin formula. The data analysis technique used is multiple linear regression models with Stata software version 14. The results of this study show that capital has a negative and significant effect on the production of batik MSMEs in the Proppo District. Labour and raw materials positively and significantly affect the production of batik MSMEs in the Proppo District. Capital, labour, and raw materials positively and significantly affect the production of batik MSMEs in the Proppo District. Keywords: Capital, Labor, Raw Materials, Production and Batik MSMEs